ANALISIS PEMBERIAN ASI TIDAK EKSKLUSIF DAN SUSU FORMULA SEBAGAI PENYEBAB GROWTH FALTERING (GONCANGAN PERTUMBUHAN) PADA BAYI - Purnamasari, Dyah Umiyarni (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2008)
Background : Poor growth in infants can be indicated by a decrease in WAZ score, and is started in 2 to 6 month. Growth faltering can be continued to growth failure and it is influenced by baby feeding, such as breasfeesing and formula feeding. Therefore important to analyses no-exclusive breastfeeding and formula feeding to be determinants factors of growth faltering in infant. Methods : This Observational study was conducted in a case control design at Kangkung subdistrict. Cases were the subjects who had growth faltering, and controls were the subjects who had normal growth, both groups of 36 included subject in each group. The determinan variables investigated were no-exclusive breastfeeding and formula feeding, Analisis was conducted by logistic regression and population attribute risk (PAR). Result : About 49 (69,1%) infants got no-exclusive breastfeeding, and about 22 (30,5%) infants got formula feeding. Based on results bivariat logistic regression analyses, showed that both of signicant : No-exclusive breastfeeding (OR = 3.30; 95% CI : 1.15-9.52; PAR = 0.61), and formula feeding (OR = 2.96; 95% ci : 1.03 - 8.53 PAR = 0.38). Conclucion and Suggestion : No-exclusive breastfeeding and formula feeding to be determinants factors of growth faltering in infant aged 2-6 months. It is recomended to transfer knowledge about the importance of exclusive breastfeeding to prevention growth faltering in infancy.